Élelmiszer-biztonság: vaddisznó szövetek nehézfémszennyezettségének vizsgálata - Lénárt, Zoltán; Bartha, András; Laczay, Péter; Budai , Péter; Lehel , József (GEORGIKON FOR AGRICULTURE, 2020)
The concentration of different heavy metals (arsenic, mercury, cadmium, copper, lead) was investigated by ICP-OES method in muscle and fat tissue of wild boars (Sus scrofa scrofa). The samples of 10 males and females were collected in hunting area in Közép-Dunántúl region of Hungary. The concentration of arsenic and mercury was below the limit of detection in every sample (muscle, fat) of males and females, similarly to cadmium. The amount of copper was not above the regulated maximal levels. The concentration of lead in the muscle exceeded the regulated maximal levels. Based on our data, the consumption of tissues of the studied wild boar is objectionable from food-safety aspect and poses risk to the consumer due to the lead contents over the legal tolerable limits.